Anthracycline-induced cardiotoxicity - Ferreira, Ana Lúcia dos Anjos [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Bentham Science Publishers, 2008)
The anthracyclines constitute a group of drugs widely used for the treatment of a variety of human tumors. However, the development of irreversible cardiotoxicity has limited their use. Anthracycline-induced cardiotoxicity can persist for years with no clinical symptoms. However, its prognosis becomes poor after the development of overt heart failure, possibly even worse than ischemic or idiopathic dilated cardiomyopathies. Due to the successful action of anthracyclines as chemotherapic agents, several strategies have been tried to prevent/ attenuate their side effects. Although anthracycline-induced injury appears to be multifactorial, a common denominator among most of the proposed mechanisms is cellular damage mediated by reactive oxygen species. However, it remains controversial as to whether antioxidants can prevent such side effects given that different mechanisms may be involved in acute versus chronic toxicity. The present review applies a multisided approach to the critical evaluation of various hypotheses proposed over the last decade on the role of oxidative stress in cardiotoxicity induced by doxorubicin, the most used anthracycline agent. The clinical diagnosis and treatment is also discussed. © 2008 Bentham Science Publishers Ltd.
Keywords: Cardiomyopathy; DNA damage; Doxorubicin; Free radicals; Oxidative stress; Reactive Oxygen Species; alpha tocopherol; amifostine; anthracycline derivative; antioxidant; ascorbic acid; beta adrenergic receptor blocking agent; beta carotene; cannabinoid 1 receptor; cannabinoid 1 receptor antagonist; cyclophosphamide; cytarabine; digoxin; dipeptidyl carboxypeptidase inhibitor; DNA topoisomerase (ATP hydrolysing); doxorubicin; flavonoid; glutathione; idarubicin; inducible nitric oxide synthase; lycopene; olive oil; polyphenol derivative; probucol; razoxane; reactive nitrogen species; reactive oxygen metabolite; retinol; selenium; ubiquinone; unindexed drug; antioxidant activity; aspartate aminotransferase blood level; cardiomyopathy; cardiotoxicity; cardiovascular risk; clinical feature; creatine kinase blood level; diagnostic value; dose response; drug dose reduction; drug efficacy; drug induced disease; drug safety; drug withdrawal; early diagnosis; ECG abnormality; echocardiography; electrocardiography; follow up; health care cost; heart arrhythmia; heart failure; heart muscle biopsy; heart protection; heart transplantation; human; hypotension; incidence; lactate dehydrogenase blood level; neoplasm; nonhuman; oxidative stress; pathogenesis; primary prevention; prognosis; protein expression; QRS complex; QT prolongation; review; risk factor; side effect; single drug dose; ST segment; tachycardia; Animals; Antibiotics, Antineoplastic; Calcium; DNA Damage; Electrocardiography; Heart; Humans; Oxidative Stress